An insight on topically applied formulations for management of various skin disorders. Issue 18 (23rd November 2022) - Jain, Amit K.; Jain, Sakshi; Abourehab, Mohammed A. S.; Mehta, Parul; Kesharwani, Prashant
Abstract: Various types of skin disorders across each age group and in each part of geographical world are very dreadful. Despite not being fatal each time they are always of social and mental concern for suffering individuals, causing complications in millions of patients every day and require comparatively longer duration of treatment. Off late, various topical/transdermal formulations have been widely explored for the treatment of various skin ailments. The efficiency of topical therapy depends on various physiochemical properties of drugs like particle size, particle size distribution, partition coefficient, viscosity of dosage form, skin permeability, skin condition and the site of application. Therefore, in plenty of examples, long-acting topical formulations have shown to be markedly excellent in comparison to conventional dosage forms. The major advantages of topical formulations accrue from their demonstrated ability: (i) Reduced serious side effects that may occur due to undesirably higher systemic absorption of drug. (ii) Enhancement of drug accumulation at the desired site. (iii) Easy incorporation of enormous range of hydrophilic and hydrophobic drugs and (iv) Reduced risk of dose dumping and comparatively easy termination of drug release. The prospective applications of topically applied formulations and the deposition of pharmaceuticals into the skin are examined.